Fashion Feasibility Analysis Ready to Wear Based QR Codes in Fashion - Yosihah, Arfinda; Prasetyaningtyas, Wulansari (Journal of Creativity Student, 2026)
The development of the fashion industry  in the past decade shows that the advancement of digital technology and the intensification of the use of social media have accelerated the spread of fashion trends  globally, so that trend cycles are becoming shorter and more responsive to changing consumer tastes. This study aims to analyze the feasibility of ready-to-wear  clothing  based on embroidery QR Code reviewed from the aspects of design, size, aesthetics, sewing techniques, fashion performance, and product specialties. The research method used was  quantitative descriptive with observation sheet instruments. The object of this research consists of a set of apparel, including a crop top shirt with an outer that features an embroidered QR Code on the back and cargo pants. The research instrument was proven to be valid using Aiken's Coefficient V with the validity results of 30 assessment items having a V value ≥ 0.75. Reliability estimation was conducted using the Interclass Correlation Coefficient (ICC) with  an Average Measure value  of 0.978, which indicates excellent reliability. The results of the study showed that the feasibility of fashion based on the assessment of 5 expert panelists and 20 trained panelists on six indicators showed a very feasible category with an overall percentage of 93.68%, with the results of each indicator's assessment of 15.22%, size 15.55%, aesthetics 15.85%, sewing technique 15.58%, fashion performance 15.60% and specialties 15.88%.